2018
DOI: 10.1007/s12032-018-1112-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictive markers for efficacy of everolimus plus exemestane in patients with luminal HER2-negative metastatic breast cancer

Abstract: Metastatic breast cancer (MBC) is essentially incurable despite recent improvements in systemic therapies. We often encounter difficulties in choosing the most appropriate treatments, with optimal timing, for individual patients. Everolimus, one of the mTOR inhibitors, is usually used with endocrine therapy for MBC. Identification of predictive markers for everolimus-based treatment remains a major issue, but to date, no predictive markers have been established. We retrospectively investigated predictive marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In a gastric cell line research, expressions of pho-S6K1 Ser424 and pho-AKT Ser473 in rapamycin-resistant cells were higher than that in rapamycin-sensitive cells 46 . Another research also showed that low pho-S6 expression corresponded to response to everolimus-combined therapy and pho-S6K1 overexpression was associated with a poor prognosis 47 .…”
Section: Discussionmentioning
confidence: 96%
“…In a gastric cell line research, expressions of pho-S6K1 Ser424 and pho-AKT Ser473 in rapamycin-resistant cells were higher than that in rapamycin-sensitive cells 46 . Another research also showed that low pho-S6 expression corresponded to response to everolimus-combined therapy and pho-S6K1 overexpression was associated with a poor prognosis 47 .…”
Section: Discussionmentioning
confidence: 96%
“…We tested two proteins associated with an activated MAPK pathway, p-ERK1/2 and p-S6RP(Ser235/236) in the context of possible benefit from treatment with EVE/EXE, but there was no relation with PFS. The group of Okazaki et al ( 2018 ) have reported in only 18 ER-positive, HER2-negative MBC patients on EVE/EXE, that PFS was not significantly different between patients with high or low p-S6RP(Ser235/236) in primary tumour tissue. For the 55 patients randomised to everolimus plus tamoxifen or tamoxifen alone in the TAMRAD study, p-S6RP(Ser235/236) expression in primary tumour tissue was not associated with TTP (Treilleux et al 2015 ).…”
Section: Discussionmentioning
confidence: 98%
“…IHC analysis of primary tumour tissues from 55 out of 111 patients who participated in the randomised phase II TAMRAD study (Treilleux et al 2015 ) has shown that high levels of p-4EBP1 as well as low levels of p-AKT(Ser473) were associated with improved time-to-progression (TTP) on everolimus plus tamoxifen compared to that on tamoxifen alone. Okazaki et al (Okazaki et al 2018 ) have studied PTEN in primary tumour tissue of only 18 locally advanced BC or MBC patients on standard EVE/EXE, but found no relation with PFS. Although studies, including our attempt, on single PI3K-associated proteins in primary tumour tissue in the context of selecting MBC patients for EVE/EXE are few, it appears that this approach will not be of clinical value.…”
Section: Discussionmentioning
confidence: 99%
“…The proof of the cooperation of the ER and PI3K pathways in the advancement of tumors arose from a clinical study (19,20). A remarkable improvement was observed in the progressive defense of ER-positive breast tumor patients who underwent with everolimus treatment, an mTOR inhibitor, combined with exemestane, an inhibitor for the anti-estrogen aromatase (21,22).…”
Section: Introductionmentioning
confidence: 99%